Kupffer-Cell-Targeted Carboxylesterase 1f Knockdown Deteriorates Lipopolysaccharide/D-Galactosamine-Induced Acute Liver Failure Through Regulating Cellular Polarization in Mice - Sai Zhao; Xue Yang; Yu He; Qian Yu; Liang-Ming Liu (Canadian Journal of Gastroenterology and Hepatology)
Conclusions: Our results suggest that Ces1f plays a hepatoprotective role through regulating KC polarization, which might contribute to anti-inflammatory and antioxidative effects in LPS/D-Gal-induced ALF mice.